Tourists’ Attitudinal Factor Towards Mangrove Conservation: A Case Study of Kilim Karst Geoforest Park, Langkawi, Malaysia - Nurliyana Aqilah Asri; Fazilah Musa (e-VIBS, Faculty of Science and Natural Resources, 2021)
Kilim Karst Geoforest Park, Langkawi, is a significant spot for mangroves and geological ecotourism in Malaysia. Structured well-planned management and conservation as a tool to support sustainable ecotourism in Kilim Karst Geoforest Park are very crucial to establishing and maintaining UNESCO's Global Geopark designation. In this context, community appreciation is one of the critical approaches to the conservation of mangroves and geological areas that require address the underlying attitudes towards conservation and the needs, aspirations, history, and cultural heritage of local people. This study explores the attitudes of tourists towards mangroves conservation at Kilim Karst Geoforest Park, Langkawi. To this end, the study involved the Choice Experiments Method combined with the New Ecological Paradigm (NEP) attitude measures, and a total of 150 survey participants were assigned and interviewed using the random sampling method. Findings have shown that domestic tourists recognize other living creatures' right to control the ecosystem and have faith in human technology and innovation. Meanwhile, foreign tourists are less likely to be anthropocentric in their behaviours, explaining their hesitancy to allow human activities to alter the natural environment. Factor Analysis determined the factors in the 15 NEP statements selected by the respondents, and Principal Component Analysis (PCA) showed that the "risk of overuse" factor had the highest eigenvalues followed by the "biocentric" and the "technocentric optimist" factors. In conclusion, a proactive campaign platform could significantly increase public support for the environmental protection of mangroves in Malaysia.